Synthesis of Some 3,5-Bis-1,4-dihydro-4-phenyl 2,6-Dimethyl pyridino-2ó-amino-6ó-phenyl Pyrimidines - THORE, S.N. (Asian Journal of Chemistry, 2010)
1,4-Dihydro-4-phenyl-2,6-dimethyl-3,5-diacetyl pyridine were converted into chalcone by Claisen-Schmidt condensation with aldehydes. These chalcones were cyclized with guanidine hydrochloride to give pyrimidines.